Strategi Peningkatan Mutu dan Keselamatan Pasien di Rumah Sakit Umum Daerah Kepulauan Seribu Tahun 2019 – 2023 - Haryoso, Agus Ariyanto; Ayuningtyas, Dumilah (UI Scholars Hub, 2019)
Quality of service and patient savety now adays has become the main demand of hospital customer, even now, become one of evaluation point in hospital accreditation. Nevertheless, quality and patient savety in Kepulauan Seribu Public Hospital (RSUD Kepulauan Seribu) has not been accredited yet. RSUD Kepulauan Seribu plans to increase quality and patient savety so that can go through accreditation. This thesis aims to arrange strategies of Quality improvement and Patient Savety in Years 2019- 2023. The study in this thesis is qualitative. The study digs informations from informans to obtain internal and external factors hich used to arrange strategies. The factors then be analized with instruments such as Internal Factor Evaluation (IFE), Eksternal factor Evaluation (EVE), I-E matrix, TOWS Matrix, to obtain strategies. All employees are enthusiastic to work, and the great quantities of financial resources are obtained as strength factor, while vision and misson of hospital which are not maximal socialized, no program prioriting, and have not done quality and patien safety assessment yet are still become weakness of RSUD Kepulauan Seribu. One of the opportunity obtained in study is stake holders support, while the challenge is the capacity gap of medical officer in hospital and primary service. IFE scor is 2,40 and EFE score 2,31. RSUD Kepulauan Seribu Position of I-E matrix is in fifth cel, which mean that the best strategy to execute are hold and maintain strategies. RSUD Kepulauan Seribu, based on TOWS Matrix analysis, recommended to settle the target of organizational policy, optimize the financial resources, optimalize stakeholder cooperation, increase the employee’ knowledge, standardize employee’s upgrading, arrange priority programs, do risk management, and assess quality and patient safety.